2012
DOI: 10.1681/asn.2010111130
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicopathologic Study of Thrombotic Microangiopathy in IgA Nephropathy

Abstract: Thrombotic microangiopathy (TMA) occurs in IgA nephropathy, but its clinical significance is not well described. We retrospectively examined a series of 128 patients diagnosed with IgA nephropathy between 2002 and 2008 who had a mean follow-up of 44627 months. In our series, 53% presented with lesions of TMA, acute or organized, in arteries and/or arterioles. Among patients with TMA, 4% were normotensive, 25% had controlled hypertension, and 71% had uncontrolled hypertension. Of those with uncontrolled hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
105
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 30 publications
10
105
1
1
Order By: Relevance
“…Among patients with TMA, 4% were normotensive, 25% had controlled hypertension, and 71% had uncontrolled hypertension. Of those with uncontrolled hypertension, 26% had malignant hypertension (46). Histologically, the group with TMA had a significantly greater percentage of sclerotic glomeruli and worse tubulointerstitial fibrosis than those of the group without TMA.…”
Section: Discussionmentioning
confidence: 95%
“…Among patients with TMA, 4% were normotensive, 25% had controlled hypertension, and 71% had uncontrolled hypertension. Of those with uncontrolled hypertension, 26% had malignant hypertension (46). Histologically, the group with TMA had a significantly greater percentage of sclerotic glomeruli and worse tubulointerstitial fibrosis than those of the group without TMA.…”
Section: Discussionmentioning
confidence: 95%
“…These studies are typically described as validation studies, although none prospectively studied new cohorts; nevertheless they provide valuable corroborative evidence. Sixteen such studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] , including cohorts from Europe, North America, and East Asia were meta-analysed in a report published in 2013 21 . Lately, more studies have been published including cohorts from Iran, Europe, Japan and Korea [22][23][24][25][26][27][28] .…”
Section: Published Retrospective Validation Studiesmentioning
confidence: 99%
“…Patients whose biopsies were scored E1 were more likely to receive immunosuppressive therapy, most frequently corticosteroids, and patients with E lesions had an improved outcome if treated with corticosteroids. The two studies in which no patients received corticosteroid/cytotoxic therapy both reported that E1 was independently associated with more rapid loss of renal function and worse renal survival 8,27 . This is consistent with the reversibility of E following immunosuppression in a study reporting repeat renal biopsies after treatment 29 .…”
Section: E (Endocapillary Hypercellularity)mentioning
confidence: 99%
“…49 Also, another small study identified no mutation of CFH, CFI, and Membrane Cofactor Protein genes in 11 patients with IgAN presenting with severe thrombotic microangiopathy. 50 Clearly, larger-scale sequencing efforts will Figure 2. C3 proteolytic cascade.…”
Section: Inherited Partial Deficiencies Of Alternative Pathway Proteinsmentioning
confidence: 99%